2002
DOI: 10.1109/jsac.2002.802064
|View full text |Cite
|
Sign up to set email alerts
|

A multiplexing scheme for H.323 voice-over-IP applications

Abstract: Abstract-Voice communications such as telephony are delay sensitive. Existing voice-over-IP (VoIP) applications transmit voice data in packets of very small size to minimize packetization delay, causing very inefficient use of network bandwidth. This paper proposes a multiplexing scheme for improving the bandwidth efficiency of existing VoIP applications. By installing a multiplexer in an H.323 proxy, voice packets from multiple sources are combined into one IP packet for transmission. A demultiplexer at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…However, a compression technique was applied on the RTP header. Implementation of the proposed technique showed that combining both packets multiplexing and RTP header compression succeeded in improving bandwidth utilization, whereas, bandwidth employment improved by 72% [9].…”
Section: Related Workmentioning
confidence: 99%
“…However, a compression technique was applied on the RTP header. Implementation of the proposed technique showed that combining both packets multiplexing and RTP header compression succeeded in improving bandwidth utilization, whereas, bandwidth employment improved by 72% [9].…”
Section: Related Workmentioning
confidence: 99%
“…Other proposals for multiplexing RTP flows are [7] and [8]. They are mainly designed for VoIP, since this is a very popular service with a high overhead.…”
Section: A Multiplexing Real-time Flowsmentioning
confidence: 99%
“…Our compression is similar to the scheme proposed in [13]. It depends on the use of context-mapping tables in MUX and DEMUX to record necessary information such as RTP header for future reconstruction, source IP address for differentiation between VoIP sessions, synchronization for proper (de)compression and (de)multiplexing.…”
Section: Header Compressionmentioning
confidence: 99%
“…With this scheme, the RTP+UDP+IP header can be replaced with a 2-byte miniheader for most voice packets. We refer the reader to [13] for details. The major reason for the improved efficiency of our system here is the MUX/DEMUX scheme rather than the header compression scheme.…”
Section: Header Compressionmentioning
confidence: 99%